Local capacity building and local development in the Philippines appreciating capacity building for decentralization - Panadero, Austere A. (2002)
Capacity building is crucial to making development happen in a decentralized system. Over ten years of Philippine experience in decentralization has seen its effects in the administrative, the political and even the economic realms of local governance. These are documented in this study, beginning with the clarification of purposes for which capacity building efforts have been initiated, the major players involved and their corresponding roles, the various strategies adopted, the trends and directions that have emerged, the remaining challenges as well as the approaches instituted in managing all these concerns.
Keywords: Capacity building for decentralization -- Philippines; Decentralization -- Philippines; Local development -- Philippines; Local Government Code of 1991 -- Philippines; Local Government Units